Optimization of thermal stress thresholds on regional coral bleaching monitoring by satellite measurements of sea surface temperature - Liu, Bailu; Foo, Shawna A.; Guan, Lei (Frontiers in Marine Science, 2024)
Coral bleaching events have become more frequent in recent years due to the impact of widespread marine heatwaves. The Coral Reef Watch (CRW) program, part of the National Oceanic and Atmospheric Administration (NOAA), assesses bleaching risk by considering measures of daily coral heat stress (Hotspot, HS) and accumulated heat stress (Degree Heating Week, DHW). However, there is a mismatch between coral bleaching alerts through satellite monitoring and records of coral bleaching in the South China Sea (SCS) and its surrounding seas, where operational HS and DHW thresholds appear too conservative. Through comparison with field records of bleaching events in the SCS, this study examined the optimization of the DHW under a fixed or variable HS threshold, evaluating the accuracy of coral bleaching monitoring through a range of evaluation indices, including the Peirce Skill Score (PSS) and the Area Under the Curve (AUC). Our results show that when the DHW index was calculated based on the current operational HS threshold (1 °C), reducing the DHW threshold from 4 °C to 1.86 °C-weeks significantly improved PSS from 0.17 to 0.66, and AUC from 0.58 to 0.83. Further, by optimizing both HS and DHW, evaluation statistics were further improved, with the PSS increasing to 0.71 and the AUC increasing to 0.85. While both methods could significantly optimize the operational bleaching alert level for the SCS, the results suggest that optimization of both the HS and DHW thresholds is better than optimizing DHW alone. As marine heatwaves become more frequent, accurately predicting when and where coral bleaching is likely to occur will be critical to improving the estimation of regional coral stress due to climate change and for understanding coral reefs’ response to recurrent bleaching events.